Benefits of exercises performed in prenatal and postnatal processes of pregnancy - Korkmaz, Murat; Yücel, Ali Serdar; Yildiz, Kaya; Sahbudak, Ercan; Yildiz, Sevilay; Sevil, Ümran; Saçan, Selvinaz (Kamala-Raj Enterprises, 2018)
This research aims at determining views of health personnel regarding benefits of exercises performed properly in prenatal and postnatal processes of pregnancy. For this purpose, a questionnaire composed of two parts was applied on 570 attendees. Within the scope of the analysis, descriptive statistics, reliability analysis, Factor Analysis, Correlation Analysis, independent sample t-test, Anova analysis, Chi-square analysis, Kruskal Wallis-H and Jonckheere-Terpstra Testa analyses were used. PASW 18.0 packet program was used in the analysis of data acquired from the research. At the end of the research, it was found that views of attendees regarding the importance of sports activities physically and mentally differed by number of pregnancy, educational status, working in private or public sector and having experienced an abortion or curettage. Furthermore, it was determined that views that sports activities protected babies differed by attendees who experienced abortion or curettage and educational status; and experiencing abortion or curettage was independent from educational status. © Kamla-Raj 2018.
Keywords: Bearing; Exercise; Pregnancy; Prenatal; Sports